Chemically Stable Sulfonated Polytriazoles Containing Trifluoromethyl and Phosphine Oxide Moieties for Proton Exchange Membranes - Ghorai, Arijit; Roy, Sambit; Das, Sovik; Komber, Hartmut; Ghangrekar, Makarand M.; Voit, Brigitte; Banerjee, Susanta (ACS Applied Polymer Materials, 2020)
Polytriazoles are considered as an excellent high-performance polymer due to their outstanding set of properties. The current investigation reports the synthesis of a phosphorus-containing fluorinated diazide monomer, that is, bis[4-(4′-Azidophenoxy)-3-Trifluoromethyl phenyl] phenylphosphine oxide (PFAZ) and utilization of this compound to synthesize a set of trifluoromethyl groups and phosphine oxide containing sulfonated polytriazoles (PTPFBSH-XX). The copolymers with a different level of sulfonation (-XX =-60,-70,-80,-90) were prepared by the Cu(I) catalyst-Assisted click reaction of equimolar amounts of a dialkyne (BPALK) and a mixture of diazides having one sulfonated diazide (DSAZ) and PFAZ. The polymers were further characterized by NMR (1H, 13C, 19F, and 31P) and FTIR spectroscopy. Freestanding membranes were attained from the dissolved copolymers solution in DMSO by standard solution casting route. The membranes showcased acceptable thermal and mechanical stabilities, excellent water management with a high proton conductivity, and outstanding oxidative stability. SAXS, TEM, AFM, and cross-sectional FE-SEM studies of the membranes indicated phase-separated morphology. The oxidative stabilities of the membranes ranged over 18 h. The polytriazole PTPFBSH-90 (PFAZ/DSAZ/BPALK = 10:90:100, where the degree of sulfonation is 90%) having a weight-based ion exchange capacity (IECW) of 2.39 mequiv g-1 exhibited a high proton conductivity of 142 mS cm-1 under hydrated conditions at 90 °C. Furthermore, PTPFBSH-XX polymer membranes displayed a comparable performance in microbial fuel cell as Nafion117. The chemical oxygen demand removal results indicated that the polymeric membranes could be sustainable in bioelectrochemical systems.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Oxidative stability; Phosphine oxide moiety; Proton conductivity; Sulfonated copolytriazoles; Trifluoromethyl groups